PYCNIDIA AND CONIDIA QUANTIFICATION OF LASIODIPLODIA USING A CULTURE MEDIUM ENRICHED WITH SUGARCANE BAGASSE - Dias, Vicente Mussi-; Santosc, Adão Valmir dos; Graças, Maria das; Freirea, Machado (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The study of Lasiodiplodia species has been increasing lately due to the importance of this fungus as a pathogen of plants and animals, as well as its ability to produce chemicals ofhuman importance. For morphological and taxonomic study of this fungus in vitro, the growth factor is not a problem as it easily develops in different culture media. However, someimpediments to a sequential and complete morphological characterization of isolates may occur, such as fructification and sporulation. Nevertheless, molecular studies for this group offungi are still inconsistent (Mohali, et al., 2005; Rosado et al., 2016). Taking into consideration that morphological characterization of an isolate must be widely and completely done, we propose in this paper a new culture medium composed of salt and sugarcane bagasse (SC medium) that allows production, quantification and extraction of pycnidia and conidia of Lasiodiplodia. Assays were carried out with isolates from different sources, three of thempathogenic to coconut, cocoa and mango fruits and one endophytic isolate from Restinga. Ourresults show that the proposed medium was more translucent and allowed detection and quantification of all pycnidia produced by the isolates. There was a rapid production of pycnidia that were strongly adhered to sugarcane bagasse fibers after seven days of culture, suggesting that Lasiodiplodia uses sucrose present in the fibers as a carbohydrate source. Inaddition, it was observed significant differences between the means of pycnidia production, allowing to distinguish each isolate. The SC medium proposed here is a practical and efficient way to quantify pycnidia, structures that had been greatly neglected in the characterization and differentiation of Lasiodiplodia isolates to date.